Disassembly of F-actin cytoskeleton after interaction of Bacillus cereus with fully differentiated human intestinal Caco-2 cells - Minnaard, Jessica (2004)
In the present study, the role of direct procaryote-eucaryote interactions in the virulence of Bacillus cereus was investigated. As a model of human enterocytes, differentiated Caco-2 cells were used. Infection of fully differentiated Caco-2 cells with B. cereus in the exponential phase of growth, in order to minimize the concentration of spores or sporulating microorganisms, shows that a strain-dependent cytopathic effect develops. Interestingly, addition of 3-h-old cultures of some strains resulted in complete detachment of the cultured cells after a 3-h infection whereas no such effect was found after a 3-h infection with 16-h-old cultures. Infection of enterocyte-like cells with B. cereus leads to disruption of the F-actin network and necrosis. Even though the effect of secreted factors cannot be ruled out, direct eucaryote-procaryote interaction seems to be necessary. In addition, we observed that some B. cereus strains were able to be internalized in Caco-2 cells. Our findings add a new insight into the mechanisms of virulence of B. cereus in the context of intestinal infection.